Specifics of carbohydrate metabolism under sport-specific aerobic workloads - Dobrovolsky, O. B.; Achkasov, E. E.; Romanenkova, Y. S.; Kochetkova, E. K. (Theory and Practice of Physical Culture, 2019)
It is known that the glycogen level rise results in an increase of its reserves in the muscles and higher endurance in long-distance running sports. In the meantime, as proved by recent studies an extreme carbohydrate diet should be avoided. The present study analyzes the available literature on the issues of carbohydrate diets in long-distance running sports; and considers the role of carbohydrate barrier for competitive progress in sports. The study makes a special emphasis on the most effective and presently popular diets prioritizing carbohydrate loading (carb-up) including classical carbohydrate systems, Taper`s High Carbohydrate Intake method, Olboard method etc., with a detailed analysis of the pros and cons of every diet. The study considers the diets in detail with reasoning for inclusion of different hydrocarbons, fats and proteins, with a special emphasis on the sport-specific hydrocarbon additives. Practical applications of the above methods shall take into consideration the glycogen-driven muscular energy supply mechanism. The authors give and analyze the evidence showing that the hydrocarbon barrier overcoming technologies are much more important for the medium-class athletes than for the elite ones.